E-Learning Mobile Development of Student Structured Learning Applications during the pandemic - Andhika andhika; Manase Sahat H Simarangkir; Santo Wijaya (Jurnal KomtekInfo, 2022)
During the Covid-19 pandemic, teaching and learning activities were threatened with a decline in the quality of world education, including the quality of education in Indonesia. Students and teachers cannot interact to carry out educational activities at school. Meanwhile, in the world of education, interaction and communication are very important for the growth and development of student knowledge. If this is lost, then one generation of students could be threatened by poor quality education services caused by the covid-19 virus. Although the internet has been developed in the world of education for a long time, there are still many schools that are still unable to develop it properly for students. This is evident when the national exams were held before the Covid-19 period, there were still many schools that did not understand and understood providing facilities directly to students. This is a challenge in itself for Indonesia when the covid-19 virus attacks and paralyzes all activities. Forcing all activities to be done inside the house and reducing all activities outside the home. Learning activities and examinations are important activities that are always the focus of the school every semester. This activity previously required students to be in school, but during the pandemic this should not be done due to the government's decision to limit the spread of the virus. All schools must think hard for a solution to this problem. Schools take an important role in school activities so that the quality of education services does not decrease drastically. Private schools are no exception, whose activities come from greater than that of students' parents. While many students' parents think that if there are no activities at school, the money for school payments will be postponed. Schools only have one choice so that the learning process and exams continue, namely by using an online application that can adjust national standards and school standards. Although there are many applications in circulation, many of these applications cannot be adapted to school conditions at a low cost. Mostly, if the school wants changes to the application, then the developer sets a lot of rates that the school cannot afford. Learning and examinations are activities where the administration must also exist for reporting by schools. The reporting format, of course, is different for each school with their respective systems. With the mobile application developed by researchers and implemented according to school administration, in general, learning activities and examinations continue to run with results that can be accounted for because they have reports that are adjusted by the school.